1962
DOI: 10.18174/njas.v10i5.17583
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and redistribution of dry matter in perennial fodder crops.

Abstract: A review.-R.B. (Abstract retrieved from CAB Abstracts by CABI’s permission)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Reporting on the decline in tiller numbers he observed in Festuca rubra, Sonneveld (1962) concluded that tiller formation stopped following elongation of flowering culms and that part of the tillers was even emptied and spent. Reviewing literature on this subject, Humphreys (1966a) pointed out that inhibition of tillering has often been related to the onset of the reproductive stage, the effect disappearing during seed maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Reporting on the decline in tiller numbers he observed in Festuca rubra, Sonneveld (1962) concluded that tiller formation stopped following elongation of flowering culms and that part of the tillers was even emptied and spent. Reviewing literature on this subject, Humphreys (1966a) pointed out that inhibition of tillering has often been related to the onset of the reproductive stage, the effect disappearing during seed maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the relative activity of the isolated invertase is approximately one-third that Little is known about the functional reason for polymerization of sugars to fructosans. Many plants which contain fructosans are species which endure climatic or management induced stresses during their life cycle (Eagles, 1967;May, 1960;Sonneveld, 1962). In the past, these researchers have pointed out the importance of reserve carbohydrates to regrowth following a dormant period or harvesting.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrate reserves are important in the management of perennial forage plants. These reserves serve as an energy source for regrowth when photosynthate production does not meet the metabolic needs of the plant (Sonneveld, 1962). Several studies evaluating carbohydrate reserves in birdsfoot trefoil roots have been reported.…”
mentioning
confidence: 99%